Alcohol Consumption: Medical Implications, the Liver and Beyond. (25th March 2022) - Meza, Víctor; Arnold, Jorge; Díaz, Luis Antonio; Ayala Valverde, María; Idalsoaga, Francisco; Ayares, Gustavo; Devuni, Deepika; Arab, Juan Pablo
Abstract: Alcohol consumption represents a major factor of morbidity and mortality, with a wide range of adverse medical implications that practically affect every organ system. It is the fifth major cause of deaths in men and women and causes up to 139 million disability-adjusted life years. Solid evidence places the risk as undoubtedly correlated to the length of time and amount of alcohol consumption. While alcohol-related liver disease represents one of the most studied and well-known consequences of alcohol use, the term itself embodies a wide spectrum of progressive disease stages that are responsible for almost half of the liver-related mortality worldwide. We discuss the staged alcohol-related fatty liver, alcohol-related steatohepatitis and, finally, fibrosis and cirrhosis, which ultimately may end up in a hepatocellular carcinoma. Other comorbidities such as acute and chronic pancreatitis; central nervous system; cardiovascular, respiratory and endocrine system; renal disease; urological pathologies; type 2 diabetes mellitus and even infectious diseases are reviewed in their relation to alcohol consumption. This article reviews the impact of alcohol use on different systems and organs, summarizing available evidence regarding its medical implications. It examines current basic and clinical data regarding mechanisms to highlight factors and processes that may be targetable to improve patient outcomes. Although alcohol use is a part of many cultural and social practices, as healthcare providers we must identify populations at high risk of alcohol abuse, educate patients about the potential alcohol-related harm and provide appropriate treatment. Abstract : Short Summary: Alcohol use disorder (AUD) represents a major factor of morbidity and mortality. Alcohol-related liver disease represents one of the most studied consequences of AUD; however, it represents a disease that involves multiple systems and increases the risk of certain infections and specific types of cancer.